2012
DOI: 10.1128/jvi.07119-11
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of DNA Damage and Type I Interferon Responses Imposes an Antiviral State That Attenuates Mouse Gammaherpesvirus Type 68 Replication in Primary Macrophages

Abstract: DNA damage response (DDR) is a sophisticated cellular network that detects and repairs DNA breaks. Viruses are known to activate the DDR and usurp certain DDR components to facilitate replication. Intriguingly, viruses also inhibit several DDR proteins, suggesting that this cellular network has both proviral and antiviral features, with the nature of the latter still poorly understood. In this study we show that irradiation of primary murine macrophages was associated with enhanced expression of several antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…We and others have recently shown that the physiological DDR leads to induction of antiviral type I IFN responses (6,32), adding another important factor to the gammaherpesvirus-DDR equation. Because type I IFN suppresses MHV68 replication and reactivation in vivo (3,20) and due to virus-driven activation of the DDR in infected cells (42), it is not surprising that MHV68 uncouples the DDR-type I IFN connection in the context of lytic infection of primary macrophages (32).…”
Section: Implications For A-t and Other Ddr-linked Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have recently shown that the physiological DDR leads to induction of antiviral type I IFN responses (6,32), adding another important factor to the gammaherpesvirus-DDR equation. Because type I IFN suppresses MHV68 replication and reactivation in vivo (3,20) and due to virus-driven activation of the DDR in infected cells (42), it is not surprising that MHV68 uncouples the DDR-type I IFN connection in the context of lytic infection of primary macrophages (32).…”
Section: Implications For A-t and Other Ddr-linked Diseasesmentioning
confidence: 99%
“…Because type I IFN suppresses MHV68 replication and reactivation in vivo (3,20) and due to virus-driven activation of the DDR in infected cells (42), it is not surprising that MHV68 uncouples the DDR-type I IFN connection in the context of lytic infection of primary macrophages (32). Because virus-driven DDR induction is not limited to the MHV68 system, in the future it will be important to define the mechanism by which MHV68 interferes with type I IFN responses induced upon activation of the DDR.…”
Section: Implications For A-t and Other Ddr-linked Diseasesmentioning
confidence: 99%
“…mRNA measurement. Total RNA was harvested from cells, DNase treated, and reverse transcribed as previously described (29). cDNA was assessed in triplicate, along with corresponding negative reverse transcription (RT) reactions, by real-time PCR using an iCycler (Bio-Rad, Hercules, CA) (29,30).…”
Section: Animals and Primary Cell Cultures C57bl/6j (Bl6) Irf-1mentioning
confidence: 99%
“…Cell lysates were collected and analyzed as previously described (29,30). The antibodies used were anti-␤-actin (1:20,000; Novus Biological, Littleton, CO), anti-total Stat1 (1:3,000; Santa Cruz Biotechnology, Santa Cruz, CA), anti-IRF-1 (1:1,000; Cell Signaling Technology, Danvers, MA), anti-ssDBP (1:1,000 [30]), anti-ISG15 (1:4,000; a gift of Debbie Lenschow), and a secondary goat antimouse or antirabbit horseradish peroxidase-conjugated secondary antibody (1:25,000; Jackson ImmunoResearch, West Grove, PA).…”
Section: Animals and Primary Cell Cultures C57bl/6j (Bl6) Irf-1mentioning
confidence: 99%
See 1 more Smart Citation